Estimation of Fatigue Limits from Temperature Data Measured by IR Thermography - Hayabusa, K.; Inaba, K.; Ikeda, H.; Kishimoto, K. (Experimental mechanics, 2017)
To determine the fatigue limits of materials, fatigue testing, which is time-consuming and very expensive, is required. In order to overcome these shortcomings, estimating methods for fatigue limits based on temperature changes measured by IR camera have been proposed, and research and development of such methods have been widely conducted. In the current paper, a non-lock-in type, inexpensive IR camera was used for rotational bending fatigue testing to estimate the fatigue limit from temperature changes independent from loading signals. The results indicated that it is possible to estimate the fatigue limit from the time-temperature change curves measured under various stress conditions and converted stress amplitude-temperature change curves. The estimated results were sufficiently accurate and thus we confirmed that it is promising to estimate the fatigue limit by a non-lock-in type, inexpensive IR camera. The inflection point of a stress amplitude-temperature change curve can be determined by approximating a curve by two straight lines and finding the combination of the lines for which the sum of the residuals between the curve and the lines is the smallest. Although the temperature changes depended on the loading history (the number of loading cycles), the results of fatigue limit estimation changed little. Therefore, the proposed method is practically accurate as a simple estimation method. We also measured the behavior of stress-stroke for each loading history (the number of loading cycles) in tension-compression fatigue testing and confirmed that temperature changes during fatigue testing are associated with plastic strain energy.